The Architecture of Impunity - Tutsahnai'i, Rezib (My University)
On March 25, 2026, one hundred and twenty-three nations voted at the United Nations General Assembly to declare the transatlantic slave trade the gravest crime against humanity. The resolution itself is an insult to the dignity of every victim — those in the diaspora and those whose ancestors remained on the continent. Those who proposed it are at best ignorant of what they have done and at worst opportunists serving their own ambitions. The institution that received it, the states that adopted it, and the framework through which any remedy would flow are all instruments of the same project whose crime the resolution names. You cannot indict a crime using the instruments of the criminal.
How the United Nations, the Nation-State, and the Post-Colonial Order Render the March 25 Reparations Resolution Illegitimate
On March 25, 2026, one hundred and twenty-three nations voted at the United Nations General Assembly to declare the transatlantic slave trade the gravest crime against humanity. The resolution itself is an insult to the dignity of every victim — those in the diaspora and those whose ancestors remained on the continent. Those who proposed it are at best ignorant of what they have done and at worst opportunists serving their own ambitions. The institution that received it, the states that adopted it, and the framework through which any remedy would flow are all instruments of the same project whose crime the resolution names. You cannot indict a crime using the instruments of the criminal.
Keywords: Transatlantic slave trade; reparations; United Nations; March 25 resolution; international law; colonial sovereignty; Berlin Conference; post-colonial state; African Union; Organization of African Unity; neocolonialism; decolonization; indigenous governance; sacred governance; initiatic traditions; Middle Passage; African diaspora; continental Africa; post-colonial trap; impunity; African sovereignty; civilizational destruction; human quality; institutional legitimacy